Comparable occurances in wedding customs of the Bunjevci and the Roman speaking iinhabitants of the Balkan Penninsula - Černelić, Milana (Array, 1999)
The introductory part of the article is dedicated to Milovan Gavazzi, to the ethnology he was promoting and to its meaning and importance for the ethnology of today. The occurence of stacel, a particular wedding honoured attendant, in the Croatian heritage could not be overlooked in the scientific opus of M. Gavazzi. After a short survey of his contribution to the research of the origin of the stacel, as well as to the latest research in the early nineties, the article is introducing the elements of the Bunjevci wedding customs which might have been formed according to certain indicators in contact with the Balkan Romance speaking population. More thorough research of each particular element may bring more light to the origins of at least one part of the cultural heritage of all the Bunjevci branches, as well as to the processes of their ethnogenesis.